DEFINITION AND CHOICE OF FINANCIAL STRATEGY OF CORPORATION - V. S. Michel (Модернизация, инновация, развитие, 2015)
The current stage of economic development of theRussian Federationmakes the question of the analysis of the financial condition of corporations, as well as the development of their financial strategy. This is due to a large share of unprofitable enterprises in theRussian Federation, as well as low levels of liquidity and autonomy. Given that the financial condition of the company depends largely on the success of its activities, the analysis of the financial condition of the company paid much attention. Pledge of survival and the foundation stability of enterprises and organizations in a market economy is financial stability. Financial stability of the company is able to manipulate the funds to ensure the sustainability of production and sales through effective use, and to minimize the cost of its expansion and renovation. View of this article is devoted to the most important task of strategic management, namely the identification and selection of effective financial strategy of the corporation.